Excision of a Posterior Cruciate Ligament Cyst Using an Arthroscopic Trans-septal Approach - Abreu, Felipe Galvão (Arthrosc Tech, 2020)
Posterior cruciate ligament (PCL) cysts are rare. Although they are usually asymptomatic and benign, in a few cases they may cause knee discomfort and restricted movements. Nonsurgical treatment is the initial approach, with medication and corticosteroid injections. However, there may be treatment failures, with some cysts needing to be excised surgically. Arthroscopic excision of PCL cysts located in the posterior compartment of the knee can be technically challenging. We describe the arthroscopic excision of a PCL cyst using a trans-septal portal, which is an easy and safe method for accessing and completely removing the lesion under direct vision.